Brazilian Art under Dictatorship: Antonio Manuel, Artur Barrio, and Cildo Meireles. By Calirman Claudia - Giunta, Andrea Graciela (2013)
Based on three case studies involving works by artists Antonio Manuel, Artur Barrio and Cildo Meireles, Calirman articulates an interpretation that takes into consideration both language strategies and their parallels to international art references and the political context that activated the works' reception at the moment they were exhibited. This perspective indirectly endorses another proposal: from the post-War period onward, and especially from the 1960s onward, a mimetic or derivative relationship toward art and art centers outside Brazil can no longer be suggested. Order in the art world was no longer established on the basis of centers where novelties were produced and a receptive periphery. Instead, contacts develop in a parallel, simultaneous manner. Neo-avantgarde movements everywhere were revising the strategies of both historical and local avant-garde groups. Thus it was not only Brazilian modernism—particularly the Brazilian model of anthropophagy inaugurated by Oswald de Andrade and Tarsila de Amaral in 1928—that was being examined in Río de Janeiro, but also the modernism of Dada and Duchamp.